The algorithm of artificial intellect psychics, for creation of materials with given properties - Матченко, Т.І. (Proceedings of National Aviation University (archive), 2004)
The system of quality value parameters for qualitative reflection construction of evaluating object was proposed. The way of artificial intellect activities modelizing, which activate algorithms of synthesis creation, analysis of destruction and it’s multi-scale symbiosis was proposed. The algorithm of artificial intellect psychics was offered.